METHODOLOGY FOR DEVELOPING TECHNOLOGICAL COMPETENCE OF UNIVERSITY STUDENTS THROUGH MEDIABASED LEARNING TOOLS - Kudratov Shakhzod Nasimovich (Western European Studies, 2026)
The article highlights the opportunities for enhancing the quality of education through media-based learning technologies in the development of technological competence among university students using electronic learning tools. In particular, it examines the essence and content of developing students’ adaptability, mobility, consistency, research activity, innovation orientation, as well as their verbal and creative imagination skills
Keywords: electronic learning tools; continuous education; program; textbook